Normative data for diagnosing auditory processing disorder in Norwegian children aged 7–12 years. (2nd January 2018) - Mattsson, Tone Stokkereit; Follestad, Turid; Andersson, Stein; Lind, Ola; Øygarden, Jon; Nordgård, Ståle
Abstract: Objective : The main purpose of this research was to obtain normative data for auditory processing tests for Norwegian speaking children. Design : Participants were administered routine audiological tests and an auditory processing test-battery consisting of Filtered Words, Competing Words, Dichotic Digits, Gaps In Noise, Duration– and Frequency Pattern, Binaural Masking Level Difference and HIST Speech in Noise test. A group of 10-year-old children were retested after two weeks. The effects ear, age and gender and the test–retest reliability were investigated. Study sample : There were 268 normal hearing children aged 7–12 years who participated in the study. Results : Results revealed no differences between genders. The children showed improving performance by age on all tests, except from the Gaps In Noise and Binaural Masking Level Difference. As expected, the children showed a right ear advantage on dichotic speech tests that decreased with age. The test–retest reliability for the tests was good, with a small learning effect on the Filtered Words test. Conclusion : Normative data were established and the preferred tests for diagnosing Auditory Processing Disorder were suggested for Norwegian children aged 7–12 years.